High-Fiber Crackers Supplemented with Asparagus Hard-Stem: Impacts of Supplementation Ratios and Water Amounts in Cracker Recipe on the Product Quality - Thi Thu Tra Tran; Le Hong Ngoc Ngo; Nu Minh Nguyet Ton; Thi Hong Nhung Le; Thi Thuy Le; Van Viet Man Le (Polish Journal of Food and Nutrition Sciences)
Spears or cladophylls are edible parts of asparagus ( Asparagus officinalis L.) implemented in a human diet while its hard-stem by-products have been used for animal feeding. In this study, the asparagus hard-stem was proved to be rich in dietary fiber and total phenolics with high antioxidant capacity. Wheat flour was partially replaced by asparagus hard-stem powder (AHP) in the cracker recipe and the AHP ratios were 0 (control), 5, 10, 15, 20% of the blend weight; the nutritional constituents, antioxidant capacities, physical attributes, and sensory overall acceptability of crackers were then evaluated. As the AHP ratio increased from 0 to 20%, the dietary fiber and total phenolic contents of the fortified crackers were improved by 5.0 times and 3.2 times, respectively, while their ferric reducing antioxidant power and DPPH scavenging capacity were enhanced by 6.1 and 1.4 times, respectively. Besides, the elevated ratio of AHP also increased the product hardness and reduced its overall acceptability. The impacts of water amount used in the dough kneading on the high-fiber cracker quality were then investigated. At 20% AHP level, the appropriate water amount was 55 g/100 g of the flour blend to reduce hardness and improve overall acceptability of the fortified crackers. The study results show that AHP is a potential dietary fiber and antioxidant ingredient for high-fiber cracker making.